Analisis Pengembangan Minat, Bakat, dan Karakter Siswa Sekolah Menengah Atas Negeri 2 Muara Sugihan melalui Kegiatan Ekstrakurikuler Rohani Islam - Puji Laraswati; Muhammad Izman Herdiansyah (Universitas Batanghari Jambi, 2023)
The background in this research is to find out how the interests, talents, and character of students through Islamic Spiritual extracurricular activities at SMAN 2 Muara Sugihan. Islamic spiritual extracurricular activities aim to form students with Islamic character as well as efforts to motivate the practice of worship in schools. The formulation of the problem in this study is how are the interests, talents, and character of the students of SMAN 2 Muara Sugihan through Islamic Spiritual extracurricular activities. The type of research used in this research is qualitative research. Research instruments using observation, interviews, documentation, and triangulation. And data analysis using reduction, data presentation and data verification. The results showed that Islamic Spiritual extracurricular activities carried out at SMAN 2 Muara Sugihan were good enough to develop students' abilities in terms of interests, talents and student character. It can be seen from the process of implementing Islamic Spiritual extracurricular activities itself where there are several programs from daily programs (Dhuha and Dzuhur Prayers in congregation and reading the Qur'an), weekly programs (Islamic Studies, Muhadhoroh, Qiro'ah, Friday Prayers in congregation, and cleaning the prayer room), monthly program (dhikr in congregation), and annual program (celebration of Islamic holidays). These programs make students more interested in developing the abilities they have.